Comparing the external loads encountered during competition between elite, junior male and female basketball players - Portes, R.; Jiménez, S. L.; Navarro, R. M.; Scanlan, A. T.; Gómez, M.-A. (International Journal of Environmental Research and Public Health, 2020)
The aim of the present study was to compare external loads (EL) between elite, junior, male and female basketball players. Male (n = 25) and female players (n = 48) were monitored during 11 competitive matches (3 matches per team). EL was measured using local positioning system and microsensor technology to determine total, high-intensity (14-21 km h..1), and sprint (>21 km h..1) distance (m) covered, total (n) and relative (n min..1) accelerations and decelerations, ratio of accelerations:decelerations, and total (arbitrary units [AU]) and relative (AU min..1) player load. EL was compared between sexes overall and according to each playing position (guards, forwards, and centers). Males covered larger (p < 0.05) high-intensity and sprint distances, and completed more (p < 0.05) decelerations than females; while female players experienced a greater (p < 0.05) ratio of accelerations:decelerations. Greater decelerations (p < 0.05) were observed for males in the guard position compared to females, while more (p < 0.05) accelerations min..1 were apparent for females in the forward position compared to males. The current findings indicate di erences in EL, particularly the high-intensity and acceleratory demands, exist between elite, junior, male and female basketball players during competition and are a ected by playing position. These outcomes can be used in developing sex- and position-specific training plans, and in turn improving the physical preparedness of junior basketball players for competition demands at the elite level.